The Association between Trust in Health Care Providers and Medication Adherence among Black Women with Hypertension - Abel, Willie M.; Efird, Jimmy T. (Frontiers in Public Health, 2013)
Background: Black women have the highest prevalence of hypertension in the world. Reasons for this disparity are poorly understood. The historical legacy of medical maltreatment of Blacks in the U.S. provides some insight into distrust in the medical profession, refusal of treatment, and poor adherence to treatment regimens. Methods: Black women (N=80) who were prescribed antihypertensive medications were recruited from urban communities in North Carolina. Study participants completed the Trust in Physician and Hill-Bone Compliance to High Blood Pressure Therapy questionnaires. An exact discrete-event model was used to examine the relationship between trust and medication adherence. Results: Mean age of study participants was 48 ± 9.2 years. The majority of participants (67%) were actively employed and 30% had incomes at or below the federal poverty level. Increasing levels of trust in the health care provider was independently associated with greater medication adherence (PTrend=0.015). Conclusions: Black women with hypertension who trusted their health care providers were more likely to be adherent with their prescribed antihypertensive medications than those who did not trust their health care providers. Findings suggest that trusting relationships between Black women and health care providers are important to decreasing disparate rates of hypertension.